Role of Auxin and Nitrate Signaling in the Development of Root System Architecture - Hu, Qi-Qi; Shu, Jian-Qin; Li, Wen-Min; Wang, Guang-Zhi (Frontiers in Plant Science, 2021)
The plant root is an important storage organ that stores indole-3-acetic acid (IAA) from the apical meristem, as well as nitrogen, which is obtained from the external environment. IAA and nitrogen act as signaling molecules that promote root growth to obtain further resources. Fluctuations in the distribution of nitrogen in the soil environment induce plants to develop a set of strategies that effectively improve nitrogen use efficiency. Auxin integrates the information regarding the nitrate status inside and outside the plant body to reasonably distribute resources and sustainably construct the plant root system. In this review, we focus on the main factors involved in the process of nitrate- and auxin-mediated regulation of root structure to better understand how the root system integrates the internal and external information and how this information is utilized to modify the root system architecture.